2018
DOI: 10.1093/geroni/igy021
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Anxiety About Aging in Adult Day Care Centers and Continuing Care Retirement Communities

Abstract: Background and ObjectivesThe present study compares how 2 settings: adult day care centers (ADCCs) and continuing care retirement communities (CCRCs) fare with regard to loneliness and anxiety about aging. Loneliness is a highly prevalent and distressing subjective experience of inadequate social relations, which has negative effects on health and well-being. Anxiety about aging is defined as worries brought up by imagining the negative consequences and losses associated with old age. The study also examines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 71 publications
3
28
0
Order By: Relevance
“…Given the significance that intimate relationships play in older adults’ lives ( Carstensen et al, 2003 ), it appears that CCRCs are better capable of moving older adults from large secondary groups, to more intimate primary groups ( Olk & Gibbons, 2010 ; Perion & Steiner, 2017 ). This finding is consistent with a recent study which has found higher levels of loneliness among ADCCs’ users compared with CCRC residents ( Ayalon, 2018 ). Hence, it appears that compared with ADCCs, CCRCs are better at facilitating more intimate social interactions between older adults.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Given the significance that intimate relationships play in older adults’ lives ( Carstensen et al, 2003 ), it appears that CCRCs are better capable of moving older adults from large secondary groups, to more intimate primary groups ( Olk & Gibbons, 2010 ; Perion & Steiner, 2017 ). This finding is consistent with a recent study which has found higher levels of loneliness among ADCCs’ users compared with CCRC residents ( Ayalon, 2018 ). Hence, it appears that compared with ADCCs, CCRCs are better at facilitating more intimate social interactions between older adults.…”
Section: Discussionsupporting
confidence: 93%
“…First, the study relied on four ADCCs and four CCRCs. Although this represents a substantial number of different settings, given the very limited research on the topic conducted thus far ( Ayalon, 2018 ), to fully explore the network structure as a whole and draw firm conclusions about it, a larger number of settings is desired. The nonresponse rate in our study was similar to the nonresponse rate reported in several other studies with difficult to reach populations ( Casey, Low, Jeon, & Brodaty, 2016 ; Locker, 1993 ), yet, it certainly limits the information one can infer about the social network ( Kossinets, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, negative attitudes about aging are related to a variety of health outcomes in older adults, including lower survival rates and physical and mental health issues ( Breda & Watts, 2017 ; Han & Richardson, 2014 ). Anxiety about aging can even explain some of the relationship between one’s environment and loneliness ( Ayalon, 2018 ), suggesting that negative aging attitudes could exacerbate feelings of loneliness (see also Shiovitz-Ezra et al, 2018 ). On the other hand, positive attitudes about aging have been associated with more new friends in older adulthood ( Menkin et al, 2017 ), which could prevent loneliness.…”
mentioning
confidence: 99%
“…That study concluded that ADCCs are therefore, ineffective in alleviating loneliness (Iecovich & Biderman, ). A different study comparing loneliness in ADCCs and CCRCs has found higher levels of loneliness (Ayalon, ), as well as sparser networks and lower social reciprocity in ADCCs (Ayalon, Yahav, & Lesser, ). CCRC residents on the contrary, have generally reported substantial social benefits associated with their relocation into the CCRC (Ayalon & Greed, ).…”
Section: Introductionmentioning
confidence: 99%